Molecular Docking Study of Nigella sativa Alkaloid Compounds as the Inhibitor of Papain-Like Protease SARS-CoV-2 - Gusnia Meilin Gholam; Iman Akhyar Firdausy (Journal of Tropical Pharmacy and Chemistry, 2023)
SARS-CoV-2 causes about 66% of China’s Wuhan market workers to experience fever, dry cough, and fatigue. Black cumin (Nigella sativa) is a plant with many benefits to cure many illnesses like hypertension, headache, infection, and inflammation. This study aimed to investigate the inhibition by compounds belonging to the Alkaloid group from Black Cumin Seed to inhibit PLpro activity as a target for SARS-CoV-2. The study used five alkaloid compounds ((2E,4E)-Decadienal, (2E,4Z)-Decadienal, Nigellicine, Nigellidine, and Nigellimine) from the Black cumin seed and a PLpro SARS-CoV-2 receptor (PDB ID: 6WX4). The methods used are ligand and receptor preparation, grid box validation, molecular docking, 2D and 3D visualisation, and data analysis using Gibbs free energy, type of interaction, and contact of amino acid residues data. This study used YASARA structure and BIOVIA Discovery Studio. The results showed that Nigellidine has the highest Gibbs free energy with a -2.67 kcal/mol score, higher than VIR251. PLpro has a catalytic triad at Cys111, His272, and Asp286 residues, the compound that binds to the active site is Nigellicine found at amino acid Cys111 with Pi-Sulfur.